Grenada - A Nation Rebuilding : An Assessment of Reconstruction and Economic Recovery One Year after Hurricane Ivan - World Bank (Washington, DC, 2021)
Hurricane Ivan struck Grenada on September 7, 2004. The international and local communities responded with a massive reconstruction and recovery effort. Although the job is far from finished, the reconstruction to date is substantial. Large-scale efforts have been mounted by Grenadian Government agencies, the private sector and civil society in Grenada. Several bilateral and multi-lateral agencies as well as international nongovernmental organizations (NGOs) have provided considerable assistance. The purpose of this report is to provide an overview of the relief and reconstruction programs that have taken place through the efforts of the Grenadian authorities and outside agencies during the past year. Overall, significant reconstruction progress has been made as of October 2005. Recovery is on its way, but much remains to be accomplished if the country is to return to a stable development path. The economy, which contracted by close to 24% in the last semester of 2004, has rebounded thanks to the increased activity in the construction sector, which absorbed a large share of those left unemployed in the aftermath of the disaster.